Auditoria De Gestion A La Cooperativa De Transportes “Union Cariamanga” En La Ciudad De Loja, Periodo Enero –Diciemre 2011. - Jaramillo Quito, Sandra Karolina (2016)
This thesis is developed based on the general purpose of performing an audit to The Cooperative Management of Transports "Cariamanga Union" of the City of Loja, period January to December 2011, and then assess the fulfillment of the objectives and institutional goals; design and implementation of performance indicators to assess the fulfillment of the goals, objectives, programs and activities proposed and develop an audit report that contains comments, conclusions and recommendations. This required the implementation of audit methods and techniques in order to obtain relevant information from each component and meet the objectives for the development of the same. To meet the above objectives was used interviews and surveys to the directors of the Cooperative Transport "Cariamanga Union", then applied clear questions through internal control questionnaires in order to determine the reliability of it and by the help of methods was possible to detect significant findings to analyze and describe them through narratives and establish different performance indicators to evaluate the efficiency, effectiveness and economy of the activities of staff to then make comments and conclusions respective generating appropriate recommendations for sound decision-making required by managers and so help the achievement of goals and objectives established by the cooperative. The results found when performing the audit process are part not evaluate or staff is periodically trained, does not have adequate control of entry and exit of personnel, not complied with the provisions of the rules of procedure, etc. As corrective measures must be taken in order to monitor and verify compliance with designated responsibilities to each employee of the cooperative, being these targeted timely management of the institution for taking appropriate corrective measures in the areas examined. Also contains the conclusions and recommendations that we determined that in evaluating the three components through the proposed management audit has identified weaknesses in the internal control system is performed by noting that according to a plan annual training to staff according to their profile, has no Certificated Personnel in different departments and finally to put a clock in order to control the entry and exit of personnel working in it.